2015
DOI: 10.1103/physrevb.91.214203
|View full text |Cite
|
Sign up to set email alerts
|

Atomic dynamics in Zr-(Co,Ni)-Al metallic glass-forming liquids

Abstract: The microscopic transport and the macroscopic flow behavior of Zr-(Co,Ni)-Al melts are systemically investigated using containerless processing techniques. A remarkable decrease of the Co, Ni self-diffusion coefficient and increase of the melt viscosity upon alloying Al, are observed. In contrast to many other metallic glass-forming liquids, the average packing fraction of the melt derived from the measured macroscopic density decreases. Our study indicates that chemical interactions of Al with transition meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…Moreover, Angell´s fragility factor m exhibited a maximum in the composition range with the best GFA, which is opposite to what is expected [4,22,24]. However, the kinetic effects may be crucial for the enhancement of GFA in TL-TE alloys on addition of Al [49]. Simultaneously, Δχexp/χa shows a sharp maximum at 33.3 at.% Cu where the stable bct CuZr2 compound forms ( Fig.…”
Section: Resultsmentioning
confidence: 71%
“…Moreover, Angell´s fragility factor m exhibited a maximum in the composition range with the best GFA, which is opposite to what is expected [4,22,24]. However, the kinetic effects may be crucial for the enhancement of GFA in TL-TE alloys on addition of Al [49]. Simultaneously, Δχexp/χa shows a sharp maximum at 33.3 at.% Cu where the stable bct CuZr2 compound forms ( Fig.…”
Section: Resultsmentioning
confidence: 71%
“…This can be explained if one considers that smaller Cu atoms tend to surround larger Zr atoms and to nest into the corners of the d-wave outer shell of Zr. We also note here that similar electronic interactions affect the slowing down of the dynamics in Zr-(Cu/Ni/Co) melts with Al additions via an enhanced short-range packing between the Al and late-transition metal species [43][44][45].…”
Section: B Fitting Protocol Of G(r) Datamentioning
confidence: 59%
“…Note that for the packing fraction, derived from the macroscopic density of the melt, a statistical random distribution of atoms is assumed, while Zr-Ni melts are known to exhibit pronounced chemical short range order. 19,20 However, unlike the ternary Zr-(Co,Ni)-Al melts, 35 here an average molar volume (packing fraction) can still capture the composition dependence of the liquid viscosity qualitatively.…”
mentioning
confidence: 94%
“…We have shown that for the binary Zr-Ni system atomic packing qualitatively controls the viscosity. Combined with low temperature viscosity data, this allows to investigate the kinetic contribution to the glass formation 35 and related interesting phenomena, such as strong-fragile transitions. 6 We would like to thank the German Space Agency, Bonn, which enabled us to take part in the parabolic flight mission, and the members of the TEMPUS team for operating the TEMPUS facility.…”
mentioning
confidence: 99%